Йосип Шкловський: спогади про видатну особистість - Курок, О.; Грудинін, Б. (Краєзнавство, 2018)
Метою статті є репрезентація біографічних відомостей про видатного астрофізика ХХ століття Йосипа Самуїловича Шкловського. Методами дослідження слугували аналіз наукової та науково-популярної літератури з питань астрофізики, якими займався Йосип Самуїлович Шкловський; бесіди
з донькою вченого Аллою Йосипівною про роки дитинства Йосипа Самуїловича та його наукову діяльність. Описані експонати музеїв м. Глухів Сумської області (батьківщина ученого), які розповідають про життя і наукову творчість ученого; вперше опубліковано спогади Алли Йосипівни Шкловської про батька; подано інформацію про проведення І Міжнародної науково-практичної конференції, присвяченої 100-річчю від дня народження Йосипа Самуїловича Шкловського (м. Глухів, 6–8 жовтня 2016 р.). The purpose of the article is representing the biographical information about the outstanding astrophysicist
of the twentieth century, Yosyp Samuyilovych Shklovs’ky who belongs to the bright representatives of the twentieth
century science. He was an outstanding astrophysicist, Corresponding Member of the Academy of Sciences
of the USSR, a member of many foreign academies and he significantly influenced the development of astrophysics
in the second half of the twentieth century.
Yosyp Shklovs’ky was the founder of the powerful school of the all-wave evolutionary astrophysics, the
author of the modern theory of the solar corona, fundamental researches on the physics of interstellar environment
on the basis of atomic and molecular radio spectroscopy data; the author of works on the connections
between cosmic masers with the spheres of forming stars and planetary systems, the evolution of stars from
the main sequence through the stage of red giants to planetary nebulae and white dwarfs, the development of
cosmic explosions of supernovae and nuclei of galaxies, relic cosmological radiation and the problem life in
the universe.
The problem of the existence of life in the universe takes a separate place in the scientific works of Yosyp
Shklovs’ky. This extremely complicated problem is a complex one and attracts the attention of a wide range of
scientists in cybernetics, astronomy, radiophysics, biology, sociology and even economics.
Yosyp Samuyilovych was among the first to start looking for the existence of extraterrestrial mind. It was
an unusual and daring idea for a scientist of the twentieth century! Y. Shklovs’ky did not find an extraterrestrial
mind, moreover, he proved that it did not exist, but at the same time he fulfilled an important mission – having
caused emerging the generation of enthusiasts who are looking for it till present day. Yosyp Shklovs’ky was the
first to dare to apply a profound scientific analysis to the theme of life in space. Understanding this problem
was the issue that he decided to direct knowledge of modern physics, biology and astronomy on. To fulfil this,
he had to master all of these disciplines.
The research methods included the analysis of the scientific and popular science literature on astrophysics
issues, which were studied by Yosyp Samuyilovych Shklovs’ky; conversations with the scientist’s daughter Alla
Yosypivna about the years of childhood of the scientist and his scientific activities. The exhibits of the museums
of the town of Hlukhiv, Sumy region (the birthplace of the scientist) representing the life and scientific activity
of the researcher were highlighted; Alla Yosypivna Shklovs’ka’s memoirs about her father were first published;
information on the 1st International Scientific and Practical Conference devoted to the 100th anniversary of
the birth of Yosyp Samuyilovych Shklovs’ky (Hlukhiv, October 6–8, 2016) was presented. Целью статьи есть репрезентация биографических данных про выдающегося астрофизика
ХХ столетия Иосифа Самуиловича Шкловского. Методами исследования стали анализ научной и научно-популярной литературы по проблемам астрофизики, которыми занимался Иосиф Самуилович Шкловский; беседы с дочерью ученого Аллой Иосифовной про годы детства Иосифа Самуиловича и его научную деятельность. Описаны экспонаты музеев г. Глухов Сумской области (родина ученого),
рассказывающие о жизни и научном творчестве Иосифа Шкловского; впервые опубликованы воспоминания Аллы Иосифовны Шкловской об отце; подано информацию о проведении І Международной научно-практической конференции, посвященной 100-летию со дня рождения Иосифа Самуиловича
Шкловского (г. Глухов, 6–8 октября 2016 г.).